2023
DOI: 10.1111/acel.13961
|View full text |Cite
|
Sign up to set email alerts
|

AAV‐Mediated nuclear localized PGC1α4 delivery in muscle ameliorates sarcopenia and aging‐associated metabolic dysfunctions

Abstract: Sarcopenia is characterized of muscle mass loss and functional decline in elder individuals which severely affects human physical activity, metabolic homeostasis, and life quality. Physical exercise is considered effective in combating muscle atrophy and sarcopenia, yet it is not feasible to elders with limited mobility. PGC‐1α4, a short isoform of PGC‐1α, is strongly induced in muscle under resistance training, and promotes muscle hypertrophy. In the present study, we showed that the transcriptional levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Regarding both aspects, our data here pave the way to several compelling questions for the aging muscle, including shared/differential mechanisms of PGC1alpha isoforms and which co-factors are engaged by the GR in beneficial versus deleterious muscle contexts. It is interesting to emphasize that our findings are consistent with not only genetic experiments with PGC1alpha isoforms 810,40 but also with scattered reports regarding the metabolic link between PGC1alpha activation and growth. For instance, PGC1alpha was found to integrate oxidative and growth pathways downstream of caloric restriction 11 , a generally positive intervention in the context of aging and muscle health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding both aspects, our data here pave the way to several compelling questions for the aging muscle, including shared/differential mechanisms of PGC1alpha isoforms and which co-factors are engaged by the GR in beneficial versus deleterious muscle contexts. It is interesting to emphasize that our findings are consistent with not only genetic experiments with PGC1alpha isoforms 810,40 but also with scattered reports regarding the metabolic link between PGC1alpha activation and growth. For instance, PGC1alpha was found to integrate oxidative and growth pathways downstream of caloric restriction 11 , a generally positive intervention in the context of aging and muscle health.…”
Section: Discussionsupporting
confidence: 91%
“…PGC1alpha impact on metabolism is balanced at the level of its splice variants 7 . Besides the canonical longer PGC1alpha-isoform 1 that regulates mitochondrial biogenesis and function, the shorter PGC1alpha-isoform 4 has been identified in mice and humans from an alternative transcription start site 8 and is sufficient to increase muscle mass and strength in cachectic muscle 9 and sarcopenia 10 . A previous study with caloric restriction reported correlations between PGC1alpha upregulation in aging muscle and activation of growth pathways in addition to mitochondrial function 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Both base and prime editors are large (>197kDa) fusions consisting of a Cas9 fused to DNA targeted enzymatic domains (41)(42)(43)(44), and additional fusions are being employed for epigenetic editing, transcriptional activation, and transcriptional repression (8,9,(45)(46)(47). Many other myonuclear-targeted cargoes are also under development, such as a DUX4 dominant negative for Facioscapulohumeral dystrophy (48), Pumilio-PIN fusions for myotonic dystrophy (49), and PGC1a for sarcopenia (50). All of these approaches can in principle benefit from the enhanced myonuclear propagation and protein stability provided by Myospreader or other NLS/NES combinations.…”
Section: Discussionmentioning
confidence: 99%